Environmental factors’ influence on blood pressure variability and circadian rhythm in arterial hypertension patients - A. P. Sharandak; L. L. Kirichenko; Zh. Yu. Dvoryanchikova; O. S. Tseka; A. P. Korolev; M. V. Koroleva; E. T. Lilyin (Кардиоваскулярная терапия и профилактика)
Aim. Using twin models, to demonstrate the leading role of environmental factors for blood pressure (BP) variability (Var) and circadian rhythm (CR) parameters. Material and methods. In total, 74 twin pairs with normal BP (mean age 42,4±2,3 years) and 64 twin pairs with arterial hypertension (AH) (mean age 52,76±3,2 years) were examined. Simultaneous pair-wise 24-hour BP monitoring (BPM) was performed with АВРМ-02 device (“MEDITECH”, Hungary). Var of mean systolic BP (VMSBP), mean diastolic BP (DBP), mean hemodynamic BP (VMBP) and mean pulse BP (VPBP) was investigated, as well as Var of mean heart rate (HR) and circadian indices (CI) for SBP, DPB and MBP. Results. In participants with normal BP, environmental factors played the leading role in forming BP Var parameters. In AH patients, hereditary factors input in daytime VPBP was about 21%. Nighttime VSBP and VMBP were genotype-influenced by 22% and 36%, respectively. Random environmental factors were more influential for CIin AH patients; in AH-free individuals, environmental and hereditary factors were equally influential. Conclusion. Random and systematic environmental factors play a leading role in forming BP Var and CR in AH twins, with minimal role of hereditary factors.